Algorithmic Game Theory 5th International Symposium, SAGT 2012, Barcelona, Spain, October 22-23, 2012. Proceedings - Serna, Maria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 5th International Symposium on Algorithmic Game Theory, SAGT 2012, held in Barcelona, Spain, in October 2012. The 22 revised full papers presented together with 2 invited lectures were carefully reviewed and selected from 65 submissions. The papers present original research at the intersection of Algorithms and Game Theory and address various current topics such as solution concepts in game theory; efficiency of equilibria and price of anarchy; complexity classes in game theory; computational aspects of equilibria; computational aspects of fixed-point theorems; repeated games; evolution and learning in games; convergence of dynamics; coalitions, coordination and collective action; reputation, recommendation and trust systems; graph-theoretic aspects of social networks; network games; cost-sharing algorithms and analysis; computing with incentives; algorithmic mechanism design; computational social choice; decision theory, and pricing; auction algorithms and analysis; economic aspects of distributed computing; internet economics and computational advertising.
Solution concepts in game theory -- Efficiency of equilibria and price of anarchy -- Complexity classes in game theory -- Computational aspects of equilibria -- Computational aspects of fixed-point theorems.-Repeated games -- Evolution and learning in games -- Convergence of dynamics -- Coalitions, coordination and collective action -- Reputation, recommendation and trust systems -- Graph-theoretic aspects of social networks -- Network games -- Cost-sharing algorithms and analysis -- Computing with incentives -- Algorithmic mechanism design -- Computational social choice -- Decision theory, and pricing.-auction algorithms and analysis -- Economic aspects of distributed computing -- Internet economics and computational advertising.
Keywords: Computer science; Electronic data processing; Computer simulation; Computer Science; Simulation and Modeling; e-Commerce/e-business.; Models and Principles; Computers and Society; Numeric Computing; Probability and Statistics in Computer Science